Analysis of Diagnosis Delay on Lung Tuberculosis Patient in Porong Primary Health Care, East Java, Indonesia - Muhammad Bagus Fidiandra; Budiono Budiono; Soedarsono Soedarsono (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: The duration of diagnosis delay in tuberculosis (TB) control strategy is one of the problems in TB control program. There are a lot of adverse effects, such as increasing the risk of people to become more prone to TB transmission, infectivity period, and worsening the patient’s condition that can furthermore increase the mortality and morbidity numbers. This study aimed to analyze the delay behavior in the society, specifically in Porong, East Java. Methods: The respondents filled a questionnaire, the answer was crosschecked and complemented with the medical record on the clinic. The data collected then were analyzed with binary logistic regression using SPSS.Results: From the total of 22 samples in this study, 11 of them were classified to be delayed (patients checked their symptoms 2 weeks after the symptoms started to appear). Some factors that might have an effect on the patient’s delay were education level, the patient’s knowledge about TB, and occupation that lead to the patient’s business. Meanwhile, factors like age, gender, and the distance between the patient’s house and the health facility might have an insignificant effect.Conclusion: Duration of patient delay contributed significantly to the duration of diagnosis delay, with the median duration of 29 days. Meanwhile, the duration of system delay that was found only ranging at 0-3 days. In this study, however, evidence of the independent factors might have an effect on the patient’s tendencies to delay treatment that had not yet proven by statistical analysis.